2021
DOI: 10.1053/j.gastro.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Aldafermin, an Engineered FGF19 Analog, in a Randomized, Double-Blind, Placebo-Controlled Trial of Patients With Nonalcoholic Steatohepatitis

Abstract: N ASH affects more 80 million people worldwide and represents one of our most urgent and neglected global health crises, with broad implications on public health. 1,2 It is associated with increased risks of cirrhosis, hepatic decompensation, hepatocellular carcinoma, liver transplantation, and death. The prevalence of NASH and NASH-related end-stage liver disease are predicted to increase significantly over the next decade. 3 There are currently no approved therapies for NASH.NASH is characterized histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(148 citation statements)
references
References 41 publications
2
145
0
1
Order By: Relevance
“…In a longer-term 24-week study in NASH patients, daily administration of 1 mg aldafermin led to an approximately 30% placebo-adjusted relative reduction in liver fat while reducing ALT by about 45% from baseline. However, statin co-administration was required in more than 95% of treated subjects to mitigate the increase in LDL-cholesterol, which was also observed previously at higher doses (306). This study confirmed that aldafermin treatment did not improve glycemic control.…”
Section: Differentiation Between Analogs Of Fibroblast Growth Factorsupporting
confidence: 88%
See 2 more Smart Citations
“…In a longer-term 24-week study in NASH patients, daily administration of 1 mg aldafermin led to an approximately 30% placebo-adjusted relative reduction in liver fat while reducing ALT by about 45% from baseline. However, statin co-administration was required in more than 95% of treated subjects to mitigate the increase in LDL-cholesterol, which was also observed previously at higher doses (306). This study confirmed that aldafermin treatment did not improve glycemic control.…”
Section: Differentiation Between Analogs Of Fibroblast Growth Factorsupporting
confidence: 88%
“…While a similar effect does not appear to have been reported for FGF19, this indirect antifibrotic effect of FGF21 suggests that FGFR4 is unnecessary for inhibition of Kupffer cell-HSC signaling. Third, analogs of FGF21 and FGF19 appear to reduce markers of liver injury (ALT) and fibrosis (Pro-C3) to a similar extent in humans (245,306), consistent with FGFR4 agonism not being required in vivo, while being associated with an undesirable increase in LDL-C.…”
Section: Differentiation Between Analogs Of Fibroblast Growth Factormentioning
confidence: 72%
See 1 more Smart Citation
“…Other agents targeting global metabolic pathways have shown benefit in phase II clinical trials, including analogs of fibroblast growth factor 19 (FGF-19), 326 fibroblast growth factor 21 327 and thyroid hormone receptor β agonizts. 328 In addition to agents targeting global pathways, there are also agents specific to hepatic lipid metabolism.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…However, no placebo group was included in the trial and the significance of these effect needs to be confirmed. The data was recently confirmed in a 24 weeks trial (78 patients with F2/F3) where fibrosis improvement (>1) and no worsening of NASH was observed in 38% of patients treated with Aldafermin versus only 18% in the placebo group ( 214 ). NASH resolution with no worsening of fibrosis was observed in 24% of patients receiving Aldafermin compared to 9% in the placebo group ( 214 ).…”
Section: Clinical Findingsmentioning
confidence: 67%